Pengaruh Model Pembelajaran Project Based Learning Berbantuan Media Canva Terhadap Keterampilan Menulis Teks Eksposisi Siswa Kelas X Sma Negeri 2 Sawahlunto - Putri, Isya Parmai; Ramadhan, Syahrul; Abdurahman, Abdurahman; Putri, Delsy Arma (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECT OF CANVA'S MEDIA-ASSISTED PROJECT-BASED LEARNING MODEL ON THE EXPOSITION TEXT WRITING SKILLS OF CLASS X STUDENTS OF SMA NEGERI 2 SAWAHLUNTO This study aims to describe and analyze the influence of the Project Based Learning (PjBL) model assisted by Canva media on the expository text writing skills of 10th-grade students at SMA Negeri 2 Sawahlunto. This research focuses on three aspects: expository text writing skills without using PjBL assisted by Canva media, expository text writing skills using PjBL assisted by Canva media, and the influence of the PjBL model assisted by Canva media on students' expository text writing skills. This type of research is quantitative with an experimental method. The research design used in this study is the Control-Only Group Posttest Design. The sample in this study consisted of 36 people. The sample was selected based on the purposive sampling technique. The sample in this study used two class groups: an experimental class and a control class. Based on data analysis and discussion, three things were concluded. First, the skill of writing expository texts using the project-based learning model assisted by Canva media for class X students at SMA Negeri 2 Sawahlunto is at the Good (B) qualification with an average of 84.26. Second, the skill of writing expository texts without using the project-based learning model assisted by Canva media for class X students at SMA Negeri 2 Sawahlunto is at the More Than Sufficient (LdC) qualification with an average of 68.27. Third, the results of the hypothesis test conducted show that t-count t-table (6.03 1.69) at a significance level of a = 0.05 and a confidence level of 95%. This indicates that there is a significant influence in the use of the project-based learning model assisted by Canva media on the skill of writing expository texts for class X students at SMA Negeri 2 Sawahlunto.